The Structure of the Methodology "Motivation for the Adoption of an Orphan Child by a Foster Family" - Oslon V.N.; Odintsova M.A.; Semya G.V.; Kolesnikova U.V. (Психолого-педагогические исследования)
The results of validation of a new version of the methodology "Motivation for the adoption of an orphan child by a foster family" (author V.N. Oslon) are presented. The analysis allowed us to identify 9 scales (types of motivation), as well as to clarify their content. All nine scales have good internal consistency (Cronbach's alpha from 0.703 to 0.937). The convergent validity of the tool is proved. At the level of high statistical significance, the scales of the questionnaire correlate with the results obtained by standardized methods: "Family Viability Scale" M.T. Sixby (adaptation by E.S. Gusarov, M.A. Odintsova, M.G. Sorokova), "Questionnaire of emotional Intelligence" (D.V. Lyusin), "Short Questionnaire of the Dark Triad" (adaptation by M.S. Egorov, M.A. Sitnikov, O.V. Parshikov); questionnaire "Big Five" by L. Goldberg (adaptation by G.G. Knyazev, L.G. Mitrofanov, A.V. Bocharov). The methodology "Motivation for the adoption of an orphan child by a foster family" is capable of performing a prognostic function and can be used by specialists of the SPR to select resource replacement families for an adopted child, as well as to track the dynamics of changes in motivation in the process of preparing potential foster parents, actualization and mobilization of types of motivation adequate to the tasks of raising an orphan child, neutralization and correction of the inadequate ones.